A Pedagogical Experience to Delve Into Students' Sense of Cultural Belonging and Intercultural Understanding in a Rural School - Bertha Ramos Holguín; Jahir Aguirre Morales; Carmen Matilde Hernández (Asociación Colombiana de Profesores de Ingles, 2012)
Rural education has been the focus for several research studies which reveal a tendency to include students' home context in the curriculum. Considering the aforementioned statement, this article aims to share a pedagogical experience which was carried out in a rural school in Guavatá, Santander, Colombia. The main purpose of this experience was to integrate eleventh graders' rural context through the design of curricular units. After implementing the curricular units, information was collected through a journal, a semi-structured interview, and students' surveys. The outcomes of the experience showed that aspects such as students' sense of cultural belonging and intercultural understanding were enhanced.